حل المنازعات الضريبية بالطريق الإداري - العموري محمد; الفتى ديما (Latakia University Journal - Economic and Legal Sciences Series, 2017)
ريبية المهمة، والجديدة والتي تهدف إلى إيجاد حل للمنازعة الضريبية – التي تنشأ بين المكلف والإدارة الضريبية في معرض تطبيق أحكام التشريع الضريبي – قبل وصولها إلى القضاء بهدف تخفيف العبء عن القضاء من خلال حلها من قبل اللجان الإدارية التي تم تشكيلها لهذا الغرض. وتتجلى أهم المحاور التي ستناقش في هذا البحث في ضرورة تحديد ماهية المنازعة الضريبية والتعرض لمفهومها، وخصائصها، والأسباب التي تؤدي إلى نشوء المنازعة بين المكلف والإدارة الضريبية، ومن ثم نبين مفهوم الاعتراض، شروطه، وآثاره . وبعد ذلك نتطرق للبحث في اللجان الإدارية المختصة بالنظر في المنازعات الضريبية في المرحلة الإدارية من حيث تشكيلها، وتحديد آلية عملها، وقراراتها، وصولاً إلى أفضل الصيغ لحل المنازعات الضريبية التي تنشأ بين الإدارة والمكلف، ووضع الحلول المناسبة للمشاكل التي تواجه المكلف والإدارة الضريبية في معرض اللجوء إلى الطريق الإداري لحل المنازعات التي تنشأ بينهما. The present research addresses one of the new and important financial and taxation issues, namely: the resolution of tax disputes via administrative means. It seeks out to find resolutions for tax disputes that arise between the taxpayer and the tax administration when applying the revenue law where administrative committees formed for that purpose would undertake resolving these disputes before being referred to the judicial stage in order to lessen the burden laid upon the judicial stage. This research discusses the importance of identifying the nature of tax disputes, concept, characteristics, and the reasons that lead to tax disputes between taxpayers and tax administration. The study attempts to explain the concept of objection, its conditions and effects. The research also addresses the administrative committees specialized in resolving tax disputes in the administrative stage shedding the light on their formation, mechanism of work, decisions, best formulas of taxpayer-tax administration resolutions for tax disputes, and best solutions for the problems facing both the taxpayer and the tax administration in resolving tax disputes arising between them via administrative means.